Determinação simultânea de Cu, Pb, Cd, Ni, Co e Zn em etanol combustível por voltametria de redissolução adsortiva e calibração multivariada. - Nascimento, Danielle Silva do (2013)
This study seeks to discuss the use of multivariate calibration techniques in the development of a methodology for simultaneous determination of Cu, Pb, Cd, Ni, Co and Zn at trace level using differential pulse adsorptive stripping voltammetry (DPAdSV). A hanging drop mercury electrode (HDME) was employed as working electrode. The calibration set was assembled by using a Brereton s design, performing 25 replicate mixtures. The different linear ranges were selected from univariate models, and verified using tests of lack of fit and significance by the ANOVA (Analysis of Variance) study. The studied ranges were Cu (0,30 3μg L-1), Pb (1 - 10μg L-1), Cd (0,5 - 5μg L-1), Ni (0,3 - 3μg L-1), Co (0,09 0,5μg L-1) e Zn (0,6 - 6μg L-1). The voltammograms were preprocessed with the algorithms AsLS (asymmetric least squares) and icoshift (interval-correlation-shifting) in order to perform baseline correction and peak alignment, respectively. The following multivariate calibration algorithms were evaluated: partial least-squares regression (PLS) and multiple linear regression with prior variable selection by successive projections algorithm (SPA-MLR). For the validation of the calibration models 10 mixtures with random concentration of each analyte were used, resulting in RMSEV between 0,03 and 0,86 g L-1. As an application of the developed method in the analysis of real samples, hydrated ethyl alcohol fuel (HEAF) was chosen as target matrix. The determination of inorganic contaminants in ethanol fuel samples is important to ensure product quality and pollution control due to release of toxic metals by burning the fuel. The validated models were satisfactorily tested in commercial samples of HEAF from different gas stations of João Pessoa, Brazil.